Esophageal Surgery - Current Principles and Advances 2023
DOI: 10.5772/intechopen.106857
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Esophagectomy in Advanced Esophageal Cancer

Abstract: Even through the esophageal cancer has innumerable treatment options, its prognosis is still unsettled. Because esophagectomy is rarely curative, others therapies, such as chemoradiation emerging in advanced disease followed or not surgery. The salvage esophagectomy is an alternative for those patients with recurrent disease. Thus in this chapter the intend is show the results of the salvage esophagectomy in patients with esophageal cancer who had previously undergone chemoradiation and discussion about the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…Aquino and Leandro-Merhi [50] also demonstrated the validity of rescue esophagectomy. Out of 82 patients who underwent radiotherapy and chemotherapy after prior creation of the palliative gastric tube, 37 experienced tumor regression, with rescue esophagectomy performed by thoracotomy.…”
Section: Figurementioning
confidence: 90%
“…Aquino and Leandro-Merhi [50] also demonstrated the validity of rescue esophagectomy. Out of 82 patients who underwent radiotherapy and chemotherapy after prior creation of the palliative gastric tube, 37 experienced tumor regression, with rescue esophagectomy performed by thoracotomy.…”
Section: Figurementioning
confidence: 90%
“…Some authors have also demonstrated in recent reports that in patients submitted to exclusive chemoradiation for palliative purposes, because they have advanced tumors, there is often regression of the local stage of the disease to the me-diastinal level, and thus it is possible to perform salvage esophagectomy. (3,4,13,48,49) AQUINO & LEANDRO-MERHI (50), also demonstrated the validity of salvage esophagectomy. Of the 82 patients who underwent radiotherapy and chemotherapy after the previous preparation of the palliative gastric tube, in 37 there was tumor regression, and rescue esophagectomy was performed by thoracotomy.…”
Section: Surgical Techniquesmentioning
confidence: 94%